2018
DOI: 10.13005/bpj/1585
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Disposal Practices of Unused and Expired Medication among Health Care Professionals and Students in a Tertiary Care Teaching Hospital

Abstract: Medicines play a very significant role for treating many diseases and conditions, but at the end of the treatment it is very important to dispose them of properly. So, the knowledge and awareness of proper drug disposal are essential for safe environment. Lack of knowledge and practice can lead to various problems like environmental pollution and various health hazards directly or indirectly. Hence, the study was aimed to assess the knowledge, practice, and awareness towards disposal of unused / expired drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
30
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 6 publications
8
30
2
Order By: Relevance
“…Universally, the correct disposal of medicine poses a challenge and is receiving increasing attention [1][2][3][4][5]. A lack of knowledge about proper disposal of unused medicine can lead to serious consequences, such as an accumulation of toxins and chemicals from the medicine into the environment, unintentional overdose, and prescription drug abuse [6].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Universally, the correct disposal of medicine poses a challenge and is receiving increasing attention [1][2][3][4][5]. A lack of knowledge about proper disposal of unused medicine can lead to serious consequences, such as an accumulation of toxins and chemicals from the medicine into the environment, unintentional overdose, and prescription drug abuse [6].…”
Section: Introductionmentioning
confidence: 99%
“…Reports have confirmed a lack of knowledge among health care professionals about the significant risks of unused or expired medicine, including diversion, abuse, and accidental overdose [16]. A study by Raja et al among health care professionals reported partial knowledge about proper drug disposal and a lack of safe disposal practices [5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations